2016
DOI: 10.11606/rdg.v32i0.116671
|View full text |Cite
|
Sign up to set email alerts
|

Perdas de Solo, Razão de Perdas de Solo e Fator Cobertura e Manejo da Cultura de Cana-de-Açúcar: Primeira Aproximação

Abstract: O objetivo desse artigo é discutir a questão da erosão em áreas de cultivo de cana de açúcar. Assim, foram determinadas as perdas de solo, a razão de perdas de solo (RPS) e os valores do fator cobertura e manejo (fator C) da Equação Universal de Perdas de solo (Universal Soil Loss Equation - USLE) para a cultura de cana-de-açúcar, cultivada em solos arenosos e argilosos e em diferentes condições de relevo e de manejo. Para obter dados visando atingir tal objetivo, foram utilizadas técnicas experimentais, com a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Isso deixa evidente que áreas declivosas onde o manejo da pastagem não é adequado oferecem pouca capacidade de conservação do solo. Segundo Corrêa et al (2016) solos arenosos em regiões declivosas apresentam maiores perdas de solo, podendo ser potencializado de acordo com o uso e regime de chuvas da região.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Isso deixa evidente que áreas declivosas onde o manejo da pastagem não é adequado oferecem pouca capacidade de conservação do solo. Segundo Corrêa et al (2016) solos arenosos em regiões declivosas apresentam maiores perdas de solo, podendo ser potencializado de acordo com o uso e regime de chuvas da região.…”
Section: Resultsunclassified
“…Este resultado está em função da maior proteção física deste. Permitindo que a matéria orgânica forneça maior resistência a erosividade das chuvas da região, fator importante para solos arenosos, pois são solos de baixa coesão entre partículas, ficando mais susceptíveis aos efeitos erosivos (Corrêa et al, 2016). Mg ha -1 ano -1…”
Section: Resultsunclassified
“…Potential soil losses by water erosion were estimated by considering Brazil's land use and coverage in 2017 (Table 1). In the areas of annual and perennial crops and planted forest, the potential soil loss was estimated by considering data obtained in erosion plots (natural or simulated rain) under low usage of conservation practices such as contour tillage, terracing, and barriers for water contention and using intensive tillage methods, with deep ploughing, disc harrowing, and subsoiling, in which the soil is turned‐over and exposed to heavy and erosive rains, causing the increase of superficial water runoff (Correa, Moraes, dos Pinto, & Lupinaccci, 2016; Santos et al, 1998). Also, by considering monoculture for annual crops and lack of cover crops for perennial crops (Hernani, De Freitas, Pruski, et al, 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Based onHernani, De Freitas, Pruski, et al (2002) b Based onCorrea et al (2016) c Based on Santos et al (1998) d Based on authors' estimate(Fuentes-Llanillo, 2018), it is estimated a cost reduction of 1.5 billion US$. A reduction in costs of 0.5 billion US$ was calculated from the area of iCLF-CA in 2015, as reported by EMBRAPA (2016).3.3 |Future increase in the adoption of CA principles (2030 forecasting) 3.3.1 | Increase in ZT/CA adoption area by 2030The forecast using ZT/CA data shows that the area will increase about 34.39 Mha in 2030 (Figure2) from the 32.88 Mha in the 2017/2018 base year.…”
mentioning
confidence: 99%
“…Researchers from various places around the world have already shown that manual sampling methods are among those methods that suffer most from this problem, commonly underestimating soil losses (Lang, 1992;Zöbisch et al, 1996;Ciesiolka et al, 2006;Nikkami, 2012;Huang et al, 2019). Curiously, this literature seems to have been largely ignored in Brazil, where a manual sampling method (Veiga and Wildner, 1993) has remained the standard (Tengberg et al, 1997;Eltz et al, 2001;Volk and Cogo, 2009;Merten et al, 2015;Corrêa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%